DISEQUILIBRIUM PERAN PETANI PEREMPUAN DI NAGARI PANDAI SIKEK KABUPATEN TANAH DATAR - Indriani, Putri; Hanani, Silfia (Kafa`ah: Journal of Gender Studies, 2023)
There are women who work as farmers in Nagari Pandai Sikek District X Koto Tanah Datar. So it was found that there was a disequilibrium in the role of women farmers. This study aims to see how the form of disequilibrium that occurs in the role of women farmers. The type of research used is descriptive qualitative research method using interview, observation and documentation data collection techniques. Interviews were conducted with women farmers, daughters of farmers, husbands of women farmers and head of farmer groups. The results showed that women who work as farmers are caused by several factors, namely economic factors, education of women farmers and land factors that support agriculture. The cause of disequilibrium is the division of labor that is still entrenched in society. There are two forms of disequilibrium in the role of women farmers. First, there are dual roles of women farmers, such as women as mothers, women as wives, women taking care of children and husbands, women educating children and women playing a role in supporting the family economy. Second, the occurrence of role conflict, the form of role conflict is the problem of child care, homework help, communication and interaction with family, time to be with family, setting priorities and work pressure.This research needs to be done in order to be able to see whaat forms will occur if woman experience disequilibrium in their roles.